2007
DOI: 10.1161/circulationaha.106.663112
|View full text |Cite
|
Sign up to set email alerts
|

Inductionless or Limited Shock Testing Is Possible in Most Patients With Implantable Cardioverter- Defibrillators/Cardiac Resynchronization Therapy Defibrillators

Abstract: Background-Implantable cardioverter-defibrillators and cardiac resynchronization therapy defibrillators have relied on multiple ventricular fibrillation (VF) induction/defibrillation tests at implantation to ensure that the device can reliably sense, detect, and convert VF. The ASSURE Study (Arrhythmia Single Shock Defibrillation Threshold Testing Versus Upper Limit of Vulnerability: Risk Reduction Evaluation With Implantable Cardioverter-Defibrillator Implantations) is the first large, multicenter, prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…Patients with more advanced heart failure were more likely to have high DFT in the ASSURE study. 15 In contrast, the parameters of cardiac function such as LV ejection fraction and LV dimensions did not predict high DFT in the present study, but ULV could predict high DFT. Although several studies have attempted to identify the predictive factors associated with high DFT, 27-31 it has been difficult to identify high-DFT patients without vulnerability or defibrillation testing.…”
Section: Inducibility Of Vf During Vulnerability Testingcontrasting
confidence: 91%
See 1 more Smart Citation
“…Patients with more advanced heart failure were more likely to have high DFT in the ASSURE study. 15 In contrast, the parameters of cardiac function such as LV ejection fraction and LV dimensions did not predict high DFT in the present study, but ULV could predict high DFT. Although several studies have attempted to identify the predictive factors associated with high DFT, 27-31 it has been difficult to identify high-DFT patients without vulnerability or defibrillation testing.…”
Section: Inducibility Of Vf During Vulnerability Testingcontrasting
confidence: 91%
“…A close correlation between the ULV and the defibrillation threshold (DFT) has been validated in some studies of humans and other animals, 12-14 and the safety and reliability of ICD implantation and programming of the lower first-shock strength using vulnerability testing without VF induction as a surrogate for DFT assessment has been demonstrated. [15][16][17][18][19][20][21] The present study evaluated the usefulness of vulnerability testing to confirm acceptable DFT at the time of ICD implantation and to predict high DFT (>20 J). Optimal strength and number of shocks at ULV testing to predict high DFT without inducing VF were assessed.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] The ULV is the energy threshold at which shocks can no longer induce VF. The ULV has been shown to be a reproducible estimator of the shock strength associated with 90% probability of successful defibrillation, 15 and the energy of a noninducing shock can, therefore, be a reliable test of ICD system efficacy.…”
Section: Clinical Perspective On P 1080mentioning
confidence: 99%
“…In many patients, ICD implant testing can be performed without induction of VF using methods based on the ULV. 5,6,11,14 Clinical assessment of the ULV is performed by delivering shocks coupled to overdrive ventricular pacing trains, usually at 500 ms. The pacing trains are necessary to establish a controlled electrophysiological substrate.…”
Section: Clinical Perspective On P 1080mentioning
confidence: 99%
“…Clinical studies show that in only 4% of patients shocks are ineffective in reversing ventricular fibrillation induced during ICD implantation [9,10]. These studies also showed that ineffective shocks are infrequent in patients with preserved ventricular contractility [9,10]. In the cases reported herein, we opted for no defibrillation testing.…”
Section: A B Discussionmentioning
confidence: 98%